MODERN FINANCIAL SUPPORTS IN THE FIELD OF ENTREPRENEURSHIP (International Congress on Economics, Management and Business Studies, 2026)
This article analyzes the role of modern financial instruments in the development of small and medium-sized businesses, in particular digital banking services and fintech technologies, in the field of entrepreneurship. It also highlights the importance of digital transformation in expanding access to financial resources for SMEs, simplifying lending processes, and increasing investment activity. The study examines the possibilities of increasing the efficiency of financial services and improving the business environment based on modern technologies. The results show that innovative financial solutions are an important factor in the development of small and medium-sized businesses.
Keywords: Small and medium-sized businesses, entrepreneurship, financial instruments, digital banking services, fintech, digital transformation, lending system, investment, financial inclusion, business financing